Implementasi Sistem Seleksi Perangkat Desa Formasi Kepala Dusun Berbasis Intranet Green Computing Guna Akselerasi Digitalisasi Di Desa Ngulungkulon Kabupaten Trenggalek - Suljatmiko Suljatmiko; Syamsul Sukmono Edy; Sigit Wahyudi; Eka Setyowati; Pudji Astuty (LPPM Politeknik Piksi Ganesha, 2026)
The implementation of an inclusive and modern village government bureaucracy requires the pillars of human resources that are competent, transparent, and with integrity. This community service article documents the implementation of technology updates in the form of a selection mechanism for the examination of candidates for Hamlet Heads in Ngulungkulon Village, Munjungan District, Trenggalek Regency which will be held on September 20, 2025. The main breakthrough presented was the use of a computerized exam platform based on a closed local network (intranet) combined with an environmentally friendly paradigm (Green Computing). This scheme aims to reduce the rate of environmental degradation due to paper waste (paperless system) and secure the exam database from external cyber-security interventions. This service method uses a technical-operational approach scheme which includes the preparation of independent infrastructure, the provision of digital literacy for candidates, and the execution of real exams with low computing power. The results of the activity prove that the implementation of the system runs absolutely without technical obstacles (zero crash). Through the integration of this technology, the efficiency of the logistics procurement budget can be reduced to the range of 80%, the transparency of value accuracy is boosted instantly, and the result is one selected apparatus name with an accountable and valid assessment record. This transformation is a crucial catalyst in accelerating the realization of a sustainable digital village management ecosystem